Breeding Strawberry for Higher Phytochemicals Content and Claim It: Is It Possible?. (30th November 2016) - Mezzetti, B.; Balducci, F.; Capocasa, F.; Zhong, C.-F.; Cappelletti, R.; Di Vittori, L.; Mazzoni, L.; Giampieri, F.; Battino, M.
ABSTRACT: Commercial strawberries ( Fragaria × ananassa ) are one of the most investigated berries for nutritional and nutraceutical properties. A strawberry breeding program, including inter-specific back-crosses, is now producing new genotypes with increased vitamin C, folates, and phenols combined with important commercial traits. The release of new cultivars with a high content of bioactive compounds, which may contribute to health, wellness, and reduced disease risk, is expected from this program. The ultimate goal is to properly obtain and integrate new scientific knowledge from genetic, agronomic, and biomedical studies that may bring acceptance from food agencies for specific health claims on new strawberry cultivars.